Pengaruh Biaya Produksi Terhadap Penentuan Harga Jual Pada Usaha Kuliner Ayam Penyet Berkah di Kecamatan Tembung - Khairunnida Khairunnida; Sri Hartini (Economics, Business and Management Science Journal, 2022)
This study aims to determine the effect of production costs on the selling price of the Penyet Berkah Chicken Culinary Business in Tembung District. The type of data used in this study is quantitative data. The source of data in this study is secondary data. This data collection technique is documentation. The population of this study is all company data regarding data on the number of production costs and selling prices at the Penyet Berkah Chicken Culinary Business in Tembung District. The sample of this research is company data regarding production costs and selling prices in 2018-2020. This research was conducted with simple regression analysis, hypothesis testing, and coefficient of determination. Based on the test results obtained tcount of 46,043. Then it can be seen that tcount ttable (46,063 1,690) and significant 0.000 005. It can be concluded that production costs have a positive and significant effect on the selling price. It is the same with the results of the coefficient of determination test, which is 98.4% and the remaining 1.6% is influenced by other variables.